Poliovirus serotype 2 and coxsackievirus A promote the natural recombination of poliovirus. Issue 3 (18th November 2019) - Qian, Yongjiang; Pu, Xufeng; Yu, Yu; Yu, Xintian; Kong, Liang; Liu, Lu; Wang, Hua; Shen, Hongxing
Abstract: Poliovirus (PV) is a member of the species Enterovirus C (EV‐C), which may cause irreversible paralysis and death. So, for the purpose of analyzing the evolution of PV2 to help in eradicating PVs globally, a recombination analysis was performed to verify all viral genomes of EV‐C, and we found 13 putative recombination events that produced PV1, 14 recombination events that can give rise to PV2, and 9 events that can lead to PV3. By analyzing our findings, we found that PV2 was involved in 25 of 36 PV recombination events, whereas coxsackievirus A (CVA) strains were involved in 12 of 36 PV recombination events, indicating that PV2 and CVAs play major roles in the natural recombination of PV. In addition, we found 11 of 36 breakpoint positions located in 2A region, which is the most active region of the recombination events. Highlight: The CVAs and PV2 play important roles in the natural recombination of PV. The 2A region is the most active region of the recombination events. PV2 and CVA strains play an important role in PV1 recombination, PV1 and CVA strains play an important role in PV2 recombination, and PV2 strains play an important role in PV3 recombination.